Pig kahuna pirates! - Sattler, Jennifer Gordon (Bloomsbury, 2014)
Pig brothers Dink and Fergus love playing at the beach, but when Dink wakes up from his nap in a grumpy mood, Fergus invites Dink to play with his new pirate ship of sand and gives him the starring role as pirate captain.